Reactions of halonorbornane and oxo-substituted derivatives with different anions by the electron transfer mechanism; redox catalysis in stabilized radicals - Uranga, Jorge Gustavo (2010)
Reactions of 2-bromo-, 2-chloronorbornane, 3-chloronorbornan-2-one and 3-bromocamphor with Me3Sn-, Ph2P- or PhS- ions were studied by an SRN1 mechanism in liquid ammonia or DMSO. The results show that substrates having a carbonyl group facilitate electron transfer reactions, which are impeded in the absence of such a group. However, when the free radical formed is stabilized by conjugation, the coupling reaction decreases, causing a concomitant increase in the reduction product. Theoretical studies explain the observed reactivity on the basis of a mechanism involving reductive cleavage as a function of the π-σ interactions.